Construction of Online English Offline Teaching Mode in the Era of Internet Plus - Zhang Mei (Forest Chemicals Review, 2021)
With the rapid development of Internet technology, its application in the field of education is more extensive and diversified, and plays a greater role in teaching. Grammar teaching is an important part of English teaching. The complexity of grammar in forestry English leads to the common problems of English grammar among students. Relying on the Internet technology to establish the cloud classroom intelligent platform, online and offline interactive English teaching can fully play the role of online teaching resources and information technology by combining online and offline. This method can activate the classroom and improve students’ language application ability and learning interest. Based on this, this paper analyzes the application of cloud classroom intelligent platform in English teaching. Then this paper discusses its construction method and application strategy, aiming to provide reference for relevant researchers.